A design for a market economy - Ronald Clapham (Intereconomics, 1974)
In most LDCs, the public sector and dirigisme have been allotted a vast, if not dominating, influence over the national economy. As a viable alternative to this widespread trend, the author seeks to develop an economic pattern of development policy based on the principles of market economy.
Keywords: 330; Economic Order